Crystal structure of Anoxybacillus α-amylase provides insights into maltose binding of a new glycosyl hydrolase subclass - Chai, Kian Piaw; Othman, Noor Farhan; Teh, Aik Hong; Ho, Kok Lian; Chan, Kok Gan; Shamsir, Mohd Shahir; Goh, Kian Mau; Ng, Chyan Leong (Nature Publishing Group, 2016)
A new subfamily of glycosyl hydrolase family GH13 was recently proposed for α-amylases from Anoxybacillus species (ASKA and ADTA), Geobacillus thermoleovorans (GTA, Pizzo, and GtamyII), Bacillus aquimaris (BaqA), and 95 other putative protein homologues. To understand this new GH13 subfamily, we report crystal structures of truncated ASKA (TASKA). ASKA is a thermostable enzyme capable of producing high levels of maltose. Unlike GTA, biochemical analysis showed that Ca2+ ion supplementation enhances the catalytic activities of ASKA and TASKA. The crystal structures reveal the presence of four Ca2+ ion binding sites, with three of these binding sites are highly conserved among Anoxybacillus α-amylases. This work provides structural insights into this new GH13 subfamily both in the apo form and in complex with maltose. Furthermore, structural comparison of TASKA and GTA provides an overview of the conformational changes accompanying maltose binding at each subsite.